Microporosity in aluminium foams. (1st June 2017) - Mukherjee, M.; García-Moreno, F.; Jiménez, C.; Rack, A.; Banhart, J.
Abstract: We studied microporosity in the metallic matrix of aluminium foams produced by the powder metallurgical route both with and without application of a blowing agent. Microporosity was studied in-situ in liquid metal foams as well as ex-situ in the solidified microstructures. In-situ studies were carried out using synchrotron X-rays. Quantitative analyses of the amount and distribution of microporosity inside cell walls, Plateau borders and nodes were performed on 2D micrographs and on 3D reconstructed volumes generated by X-ray tomography. We studied the influence of alloying elements, blowing agent and holding time on the amount and type of micropores. The mechanisms of microporosity formation and the evolution of microporosity via diffusion of hydrogen and by coalescence are discussed. It was observed that alloy composition and holding time have a strong influence on microporosity. Different possible strategies to control microporosity are suggested. Graphical abstract: 3D visualization obtained by X-ray tomography of the arrangement of micropores (coloured objects) in solid AlSi6Cu4 foam. Image 1